A model for the evolution in water chemistry of an arsenic contaminated aquifer over the last 6000 years, Red River floodplain, Vietnam. (15th December 2016) - Postma, Dieke; Pham, Thi Kim Trang; Sø, Helle Ugilt; Hoang, Van Hoan; Vi, Mai Lan; Nguyen, Thi Thai; Larsen, Flemming; Pham, Hung Viet; Jakobsen, Rasmus
Abstract: Aquifers on the Red River flood plain with burial ages ranging from 500 to 6000 years show, with increasing age, the following changes in solute concentrations; a decrease in arsenic, increase in Fe(II) and decreases in both pH, Ca and bicarbonate. These changes were interpreted in terms of a reaction network comprising the kinetics of organic carbon degradation, the reduction kinetics of As containing Fe-oxides, the sorption of arsenic, the kinetics of siderite precipitation and dissolution, as well as of the dissolution of CaCO3 . The arsenic released from the Fe-oxide is preferentially partitioned into the water phase, and partially sorbed, while the released Fe(II) is precipitated as siderite. The reaction network involved in arsenic mobilization was analyzed by 1-D reactive transport modeling. The results reveal complex interactions between the kinetics of organic matter degradation and the kinetics and thermodynamic energy released by Fe-oxide reduction. The energy released by Fe-oxide reduction is strongly pH dependent and both methanogenesis and carbonate precipitation and dissolution have important influences on the pH. Overall it is the rate of organic carbon degradation that determines the total electron flow. However, the kinetics of Fe-oxide reduction determines the distribution of this flow of electrons between methanogenesis, which is by far the main pathway, and Fe-oxide reduction. Modeling the groundwater arsenic content over a 6000 year period in a 20 m thick aquifer shows an increase in As during the first 1200 years where it reaches a maximum of about 600 μg/L. During this initial period the release of arsenic from Fe-oxides actually decreases but the adsorption of arsenic onto the sediment delays the build-up in the groundwater arsenic concentration. After 1200 years the groundwater arsenic content slowly decreases controlled both by desorption and continued further, but diminishing, release from Fe-oxide being reduced. After 6000 years the arsenic content has decreased to 33 μg/L. The modeling enables a quantitative description of how the aquifer properties, the reactivity of organic carbon and Fe-oxides, the number of sorption sites and the buffering mechanisms change over a 6000 year period and how the combined effect of these interacting processes controls the groundwater arsenic content.